Diagnosis and control of ovine pulmonary adenocarcinoma (Jaagsiekte). Issue 7 (25th July 2013) - Scott, Phil; Griffiths, David; Cousens, Chris
Abstract : Ovine pulmonary adenocarcinoma (OPA) is a contagious tumour of the lungs of sheep. It is also commonly known as Jaagsiekte, ovine pulmonary carcinoma or sheep pulmonary adenomatosis. OPA is generally considered a chronic wasting disease with progressive respiratory distress leading to emaciation, but it may be that early lung lesions predispose to secondary bacterial pneumonia causing sudden death despite antibiotic treatment. OPA is common in the UK and most other countries where sheep are farmed, but the disease may be grossly under‐reported because few deaths are investigated on sheep farms. Disease transmission is facilitated by close confinement such as indoor housing. Effective control, and possible disease eradication, has been hampered by the lack of a suitable diagnostic test or vaccine. This article describes the clinical features of OPA and outlines current methods of diagnosis. Issues surrounding the development of improved diagnostic tests are discussed.